Digital divides: K-12 student profiles and online learning - Mann, Bryan; Li, Wei; Besnoy, Kevin (Education Policy Analysis Archives, 2021)
Online learning for primary and secondary students has expanded significantly in the United States during the last two decades. In addition to the sustained growth of online learning, many schools and districts used online learning to respond to the coronavirus pandemic. As school leaders and policymakers move more students into online courses, they need information about which students succeed and struggle online. We examine the relationship between student traits and academic success in a statewide online learning program. We find that students identified with specific exceptionalities, students who identify as male, students from disadvantaged socioeconomic backgrounds, and students from cities or fringe rural areas were more likely to struggle in their online courses. This information comes at a vital time as school leaders seek to determine the effects of widespread online learning, make decisions about the support students will need after the pandemic ends, and develop the best online learning approaches when in-person schooling returns.